Vascular Duplex Study: A Historical Perspective - Muhammad Bashar, Abul Hasan (Cardiovascular Journal, 2021)
Ultrasound is a key investigating tool aiding diagnosis and treatment in the day-to-day medical practice nowadays. Like any other invention, ultrasound technology also has a long history strewn with successes and setbacks. From its modest beginning, it has come a long way to be applied not only in medical science but also in many other areas including navigation and warfare. Scientistsengineers, physicists, mathematicians, biomedical engineers and physicians worked relentlessly over centuries to bring about developments in the field of ultrasound technology as a whole. Medical ultrasound has a relatively recent history that has seen great dedication and commitment from researchers to achieve the degree of finesse we see today. The present article looks back on the historical aspects of ultrasound technology with a focus on medical ultrasound. Cardiovasc j 2021; 14(1): 55-60